Tourism, Art, and Unique Using Culture Products Promotion with Android-Based Applications - Priza Pandunata (INFORMAL: Informatics Journal, 2017)
The Government of Banyuwangi is actively promoting tourism, one of the most intensively promoted and most desirable is tourism and the unique art of Using where the Using (or Osing) tribe is known as the indigenous people of Banyuwangi. Some of Osing's popular cultural and artistic products that are often promoted include several dance performances, traditional rituals and traditional villages. One of the potential promotional media that can be used is the use of mobile devices, due to the large number of mobile device users. Therefore, to support the promotion of tourism, art and cultural products of Osing and to help the tourists in obtaining tourism information in Banyuwangi, then an application based on Android tourism is made. To develop an Android-based application is done through a series of stages: Requirement Analysis, Literature review, Data Collection and Data Processing, Application Design and code, and Testing and Evaluation.